A two-year survey on mosquitoes of Lebanon - Knio K.M.; Markarian N.; Kassis A.; Nuwayri-Salti N. (Parasite, 2005)
A total of 6,500 mosquitoes were identified during a two-year survey (1999-2001) in Lebanon, and these belonged to twelve species: Culex pipiens, Cx. laticinctus, Cx. mimeticus, Cx. hortensis, Cx. judaicus, Aedes aegypti, Ae. cretinus, Ochlerotatus caspius, Oc. geniculatus, Oc. pulchritarsis, Culiseta longiareolata and Anopheles claviger. Culex pipiens was the most predominant species in Lebanon, collected indoors and outdoors. It was continuously abundant and active throughout the year. Culex judaicus was a small and rare mosquito and it is reported to occur for the first time in Lebanon. On the coastal areas, Ochlerotatus caspius was very common, and proved to be a complex of species as two forms were detected. One of the vectors of malaria, Anopheles claviger, was collected from May to September, from eight sites in Lebanon. Its breeding sites were restricted to fresh, cool, and clean water in pools and wells. Most of these breeding sites were in the populated Metn County where a few indigenous cases of malaria were reported from 1997- 2000. This shows that the reported malaria cases were not imported, but caused by the bites of locally infected Anopheles females.